Chemokine Receptor-Specific Antibodies in Cancer Immunotherapy: Achievements and Challenges - Vela, Maria; Aris, Mariana; Llorente, Mercedes; Garcia-Sanz, Jose A.; Kremer, Leonor (Frontiers in Immunology, 2015)
The 1990s brought a burst of information regarding the structure, expression pattern, and role in leukocyte migration and adhesion of chemokines and their receptors. At that time, the FDA approved the first therapeutic antibodies for cancer treatment. A few years later it was reported that the chemokine receptors CXCR4 and CCR7 were involved on directing metastases to liver, lung, bone marrow or lymph nodes, and the over-expression of CCR4, CCR6 and CCR9 by certain tumors. The possibility of inhibiting the interaction of chemokine receptors present on the surface of tumor cells with their ligands emerged as a new therapeutic approach. Therefore, many research groups and companies began to develop small-molecule antagonists and specific antibodies, aiming to neutralize signaling from these receptors. Despite great expectations, so far, only one anti-chemokine receptor antibody has been approved for its clinical use, mogamulizumab, an anti-CCR4 antibody, granted in Japan to treat refractory adult T cell leukemia and lymphoma. Here we review the main achievements obtained with anti-chemokine receptor antibodies for cancer immunotherapy, including discovery and clinical studies, proposed mechanisms of action and therapeutic applications.